2022
DOI: 10.3389/fvets.2021.727063
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Patient-Side Evaluation of Endothelial Glycocalyx Thickness in Healthy Sedated Cats Using GlycoCheck® Software

Abstract: The endothelial glycocalyx (EG) determines transvascular fluid fluxes, and influences inflammation, coagulation, and capillary blood flow. The GlycoCheck® software calculates EG thickness using sidestream dark field videomicroscopy recordings. This method has not been evaluated for use in cats. The aim of the present study was to evaluate the use of GlycoCheck® for estimating EG thickness in healthy cats, and to investigate the variability of EG thickness in this population. One hundred and one healthy researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…With a median of 1.80 μm, there were no statistically significant difference compared to a median of 2.37 μm in control dogs. The PBR in our control dogs is similar to values found in healthy anesthetized dogs and healthy sedated cats in other studies ( 24 , 25 ). Our study also found that baseline PBR for dogs were comparable to studies in infants (approximately 2.5 μm), and human adults (approximately 2.0–2.2 μm) ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 90%
“…With a median of 1.80 μm, there were no statistically significant difference compared to a median of 2.37 μm in control dogs. The PBR in our control dogs is similar to values found in healthy anesthetized dogs and healthy sedated cats in other studies ( 24 , 25 ). Our study also found that baseline PBR for dogs were comparable to studies in infants (approximately 2.5 μm), and human adults (approximately 2.0–2.2 μm) ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 90%
“…Sidestream dark field imaging has been explored for veterinary use. Two studies have applied this methodology in a non-invasive way to measure the eGlx in the sublingual microvasculature of anaesthetised dogs ( Londoño et al, 2018 ) and cats ( Yozova et al, 2021 ). In horses, sidestream dark field video microscopy has been used to assess microvascular perfusion ( Mansour et al, 2021 ), but not the eGlx.…”
Section: Visualisation Of the Eglxmentioning
confidence: 99%
“…14,16 Use of SDF videomicroscopy with proprietary software has been validated for sublingual interrogation of microvascular health in humans, dogs, and cats in the critical care setting. 17,18 Moreover, use on the jejunum of healthy dogs has previously been described and quantitative parameters established. 19 As far as the authors are aware, use on diseased or devitalized canine intestine has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%